TARI NANJOAK UMOH DESA PULAU TENGAH KERINCI JAMBI DALAM SENI LUKIS REALIS KONTEMPORER - AL IKHSAN, Ir. Drs. Heldi, M.Si., Ph.D., Dra. Jupriani, M.Sn (Universitas Negeri Padang, 2018)
The purpose of creating this final artwork of art is to visualize the movement of nanjoak Umoh traditional dance in the form of contemporary realist paintings, as the efforts of traditional nanjoak umoh dance conservation from lost. Method of creating artworks done in stages: preparation, elaboration, synthesis, realization of the concept, complete the work process. Visualization of realist paintings of artwork entitled: Groak Pamukoak (Opening Movement), Groak uho nga keno luko bake(the movements of the people who got burned), Nawang uho ngasakaik (spell for the sick), proses ngambek bateng puwo (the process of taking the stem), Nanjoak Umoh (spear the house), ngasek uho nga keno luko bake (move to smoke to the burned), nuwok sing (throwing money), Groak gambek sing (taking the money movement), ngangkek uho nga sakaik mulai sihak (lifting sick person who will recover from the illness), uho nga keno luko bake sihak (the person affected from burns will heal). All works prioritize dance.Keywords: Dance, Nanjoak Umoh, Kerinci, Jambi, Contemporary Realist Painting